ANALYSIS OF THE POTENTIAL OF SELF-HELP IN DEVELOPMENT PLANNING IN BAKIDA VILLAGE, HELUMO DISTRICT, SOUTH BOLAANG MONGONDOW REGENCY (Journal of Economic, Business, and Administration (JEBA), 2024)
This internship was carried out with the aim of knowing and analyzing community self-help in development planning in Bakida Village, Helumo District, South Bolaang Mongondow Regency. This research uses qualitative methods so that it can provide an understanding of a phenomenon by using data collection techniques carried out using observation techniques, interviews and documents. The results showed that the potential for self-help in development planning in bakid a village,Helumo District, South Bolaang Mongondow Regency has been running well but thereare several focuses that need improvement, including quality in development planning in Bakida village.
Keywords: Analysis, Potential of Community Self-Help in Development Planning in Bakida Village